The Power of Parliament to Legislate Syariah Legal Profession Act: Analysis of the Provisions of the Federal Constitution: (Kuasa Parlimen Menggubal Akta Profesion Guaman Syarii: Analisis Peruntukan Perlembagaan Persekutuan) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Syariah legal practice is an important profession that contributes to the empowerment of Syariah courts in Malaysia. In empowering the Syariah courts, there is also the need for improvement to Syariah legal practice from time to time. Among the proposed improvements are the drafting of a specific act relating to the Syariah legal practice by Parliament. However, the separation of powers between the federal government and state governments is of issue in this matter, as the question then raised is whether Parliament has the power to draw u such an act. The findings of this article are that the Syariah courts' affairs fall under the State List, and that the state legislative assembly is the competent legislative body in matters pertaining to Syariah legal practice. However, Article 76 of the Federal Constitution can be proposed as a source of power for parliament to legislate such an act; the executive power, however, remains vested in the state. As a result, the relevant act will only operate in the state if the state legislative council approves a law to adopt the act.Keywords: Syarie Law; Syariah Court; Federal system; Islamic Affairs